QOLP-09. AUTONOMY DURATION AS ANALYZED BY KPS ≥ 70 CUMULATIVE TIME IN PATIENTS WITH BIOPSY-ONLY GLIOBLASTOMA (BO-GBM). A SUB-ANALYSIS OF THE TIMONE COHORT. (12th November 2021) - Harlay, Vincent; Loundou, Anderson; Boucard, Céline; Petrirena, Gregorio; Barrie, Maryline; Campello, Chantal; Autran, Didier; Padovani, Laeticia; Figarella, Dominique; Boissonneau, Sébastien; Dufour, Henry; Baumstark, Karine; et al.
Abstract: BACKGROUND: Maintenance of autonomy is a crucial and understudied issue for glioblastoma patients whose outcome is poor. Biopsy-only glioblastoma (BO-GBM) present with short survival and independence is of particular importance. Our objective was to explore their functional outcome. MATERIAL AND METHODS: A regional glioma SIRIC cohort was conducted at CHU Timone in 2014-2017 and we retrospectively reviewed the BO-GBM subgroup. We prospectively collected age, tumoral surface, treatment allocated and completed, and survival outcome. Functional independence was analyzed as a cumulative time of Karnofsky performance status (KPS) ≥ 70 from the date of diagnosis until death. We analyzed potential factors associated to time with KPS ≥ 70. RESULTS: Among 535 patients enrolled in the cohort, surgery was restricted to biopsy in 139 patients (BO-GBM). Mean tumoral surface measured on gadolinium-enhanced T1-weighted MRI was 1198 mm 2 (min: 65; max: 4515mm 2 ). Forty-seven patients were referred to radiotherapy-temozolomide (RT-TMZ), 75 considered unfitted for RT received chemotherapy upfront (CT-UF), and 17 patients were referred to palliative care. Median OS was 7.5 months (95%CI: 6.0-9.2), 14.0 months (95%CI: 9.7-18.7) and 6.0 months (95%CI: 4.6-7.7) for BO-GBM, RT-TMZ and CT-UF respectively. At diagnosis, 81 (58.3%) patients presented with self-care capacity (KPS ≥ 70%). For these patients, median time of autonomy preservation was 7.6 months (95%CI: 6.1-9.0). Median time of autonomy preservation differed according to treatment modalities: it was 8.6 months (95%CI: 5.9-11.3) versus 6.3 months (95%CI: 2.9-9.7) for RT-TMZ versus CT-UF group respectively (p< 0.001). In multivariate analysis, time with KPS ≥ 70 was correlated with age (p=0.001) and KPS at diagnosis (p< 0.001). CONCLUSION: Patients with inoperable GBM referred to radiotherapy-temozolomide present a valuable duration of functional independence, although shorter in patients not referred to RT. Duration of functional independence could be considered in addition to PFS and OS for treatment evaluation in patients with GBM.